PENGARUH EDUKASI TENTANG DIET HIPERTENSI TERHADAP SKOR KESADARAN BAHAYA HIPERTENSI DI WILAYAH KERJA PUSKESMAS AIR SUGIHAN JALUR 25 - Yora Nopriani; Lusiana; R.A. Fadila (LPPM STIKes Mitra Adiguna, 2024)
Hypertension is a degenerative disease that requires proper and serious treatment. Awareness in patients about hypertension is an important factor in achieving blood pressure control. Lack of knowledge and understanding of the dangers of hypertension will increase the risk of hypertension sufferers so that close cooperation is needed between health workers, patients and families to reduce the prevalence rate of its occurrence. The purpose of this study was to determine the effect of education about hypertension diet on the awareness score of the dangers of hypertension in the working area of the Air Sugihan Health Center, Line 25. This research was conducted in the work area of the Air Sugihan Health Center, Line 25, Bandarjaya Air Sugihan Village, Line 25 from January to February 2023. This research is a type of quasi-experimental research with a one group pre-posttest design. Based on the results of statistical tests, there was an increase in knowledge and level of awareness with a p-value, namely knowledge (p value = 0.000) and awareness (p value = 0.000) which indicated that there was an effect of education and awareness on the hypertension diet in the elderly in the working area of the Air Sugihan Health Center, Jalan 25. The conclusion in this study was that there was an increase in the average knowledge score and awareness score of hypertensive patients in the working area of the Air Sugihan Public Health Center Line 25. It is necessary to pay attention to the causes of hypertension which many people with hypertension do not know.